Literature Review: Pengaruh Defisiensi Vitamin D pada Pasien COVID-19 - Theresia Chrisanthy Kustiawan; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2023)
Background: Sun exposure contains ultraviolet light is needed by humans in terms of the formation of active vitamin D. The Coronavirus Disease 2019 (COVID-19) pandemic implementing the "stay at home” order led to a reduction in sun exposure which may have exacerbated vitamin D deficiency. In COVID-19 patients, Low vitamin D levels are associated with disease severity. Objectives: This literature study aims to see the effect of vitamin D deficiency in COVID-19 patients. Methods: A narrative study of literature is collected through several research articles published in the last two years (2020-2022) through the science web such as Google Scholar, Pubmed, dan ProQuest. Results: Vitamin D deficiency in COVID-19 patients causes a high risk of morbidity and mortality and vitamin D levels can be used as a predictor/prognosis of disease severity. Conclusions: Based on the result of literature study of collected articles, there is an effect of vitamin D deficiency in COVID-19 patients.